Original paperNon-melanoma skin cancer treated with HDR Valencia applicator: clinical outcomes - Tormo, Alejandro; Celada, Francisco; Rodriguez, Silvia; Botella, Rafael; Ballesta, Antonio; Kasper, Michael; Ouhib, Zoubir; Santos, Manuel; Perez-Calatayud, Jose (Journal of Contemporary Brachytherapy, 2014)
Purpose: Radiotherapy (RT) has played a significant role in treating non melanoma skin cancer (NMSC). High-dose-rate brachytherapy (HDR-BT) approaches have a paramount relevance due to their adaptability, patient protection, and variable dose fractionation schedules. Several innovative applicators have been introduced to the brachytherapy community. The Valencia applicator is a new superficial device that improves the dose distribution compared with the Leipzig applicator. The purpose of this work is to assess the tumor control, cosmesis, and toxicity in patients with NMSC treated with the Valencia applicator and a new regimen of hypofractionation. Material and methods : From January 2008 to March 2010, 32 patients with 45 NMSC lesions were treated with the Valencia applicator in the Hospital La Fe. The gross tumor volume was visually assessed, but the tumor depth was evaluated using ultrasound imaging. All lesions for the selected cases were limited to 4 mm depth. The prescription dose was 42 Gy in 6 or 7 fractions (biologically effective dose [BED] ≈ 70 Gy), delivered twice a week. Results: Ninety-eight percent of the lesions were locally controlled at 47 months from treatment. Ninety-three percent of patients were out at least 36 months from treatment. The treatment was well tolerated in all cases. The highest skin toxicity was grade 1 RTOG/EORTC, having resolved with topical treatment at 4 weeks in all but one case which required 2 months. There were no grade 2 or higher late adverse events. Conclusions : In patients with superficial basal cell carcinoma lesions less than 25 mm in maximum diameter, HDRBT treatment with the Valencia applicator using a hypofractionated regimen provides excellent results, for both cosmetic and local control at a minimum of 3 years follow-up. Moreover, the shorter hypofractionated regimen facilitates compliance, which is very relevant for the elderly patients in our series. Valencia applicators offer a simple, safe, quick, and attractive nonsurgical treatment option.